Mobile app to aid in health and wellness - Goh, Clarice Xinying (Nanyang Technological University, 2021)
The objective of the project is to design and develop a Mobile Application that aids users in maintaining or achieving their health goals and navigating through common medical conditions they might have. The report focuses on React Native and user interface design choices as well as the choices made when developing the application.